Al2O3 interface engineering of germanium epitaxial layer grown directly on silicon - Fitzgerald, Eugene A. (2013)
The quality of germanium (Ge) epitaxial film grown directly on silicon (Si) substrate is investigated based on the electrical properties of a metal-oxide-semiconductor capacitor (MOSCAP). Different thermal cycling temperatures are used in this study to investigate the effect of temperature on the Ge film quality. Prior to high-k dielectric deposition, various surface treatments are applied on the Ge film to determine the leakage current density using scanning tunneling microscopy. The interface trap density (Dit) and leakage current obtained from the C-V and I-V measurements on the MOSCAP, as well as the threading dislocation density (TDD), show a linear relationship with the thermal cycling temperature. It is found that the Ge epitaxial film that undergoes the highest thermal cycling temperature of 825°C and surface treatment in ultraviolet ozone, followed by germanium oxynitride (GeOxNy) formation, demonstrates the lowest leakage current of ~ 2.3×10^-8 A/cm2 (at -2 V), Dit ~ 3.5 × 10^11 cm-2/V, and TDD <; 10^7 cm^-2.